IMPLEMENTATION OF GOVERNMENT ASSET MANAGEMENT USING TERRESTRIAL LASER SCANNER (TLS) AS PART OF BUILDING INFORMATION MODELLING (BIM) - Saptari, Asep Yusup; Hendriatiningsih, S.; Bagaskara, Dony; Apriani, Levana (IIUM Engineering Journal, 2019)
Building asset management is a system for organizing building assets in order to provide information to support decision making. One part of asset management is the inventory of building assets. Asset inventory can be done based on Building Information Modelling (BIM). BIM is one of the approaches to look at the building as a large unified database that can provide different information. The research case is the inventory of local government assets, especially state university assets because in Indonesia, state university assets belong to local government assets. The first step of local government asset inventory is to do three-dimensional modelling using a terrestrial laser scanner (TLS) assisted by Autodesk Revit. A textual database is created which contains the location code and item code on the asset referring to the Regulation of the Minister of the Home Affairs Number 108 Year 2016 on the Classification and Codification of Regional Property. The database is directly integrated with the threedimensional model of the building. By doing these two things, there will be a building asset management process that is integrated with BIM and can be used to plan asset development. ABSTRAK: Pengurusan aset bangunan adalah sistem untuk menganjurkan aset bangunan untuk memberikan maklumat untuk menyokong pengambilan keputusan. Satu bahagian pengurusan aset adalah inventori aset bangunan. Penyediaan aset boleh dilakukan berdasarkan Pemodelan Maklumat Bangunan (BIM). BIM adalah salah satu pendekatan untuk melihat bangunan sebagai pangkalan data bersatu yang besar yang dapat memberikan maklumat yang berbeza. Kes penyelidikan adalah untuk inventori aset kerajaan tempatan, terutamanya aset universiti negeri, kerana di Indonesia, aset universiti negeri adalah milik aset pemerintah daerah. Langkah pertama inventori aset kerajaan tempatan adalah melakukan pemodelan tiga dimensi menggunakan pengimbas laser bumi (TLS) yang dibantu oleh Autodesk Revit. Pangkalan data teks dicipta yang mengandungi kod lokasi dan kod item aset yang merujuk kepada Peraturan Menteri Dalam Negeri Nombor 108 Tahun 2016 tentang Klasifikasi dan Pengkodifikasi Harta Daerah. Pangkalan data secara langsung disepadukan dengan model tiga dimensi bangunan itu. Dengan melakukan dua perkara ini, akan membina proses pengurusan aset yang disatukan dengan BIM dan boleh digunakan untuk merancang pembangunan aset.